HNL Dimer- A Specific Biomarker of Neutrophil Activity - In Sepsis and Antibiotics Monitoring. A Mini-Review - Venge, Per; Xu, Shengyuan; Mårtensson, Johan (Archives of Clinical and Biomedical Research, 2022)
Sepsis is a major burden to society and our health care systems. Early detection and treatment are keys to the improvement of the outcome of patients with sepsis with lower morbidity and mortality. We show in this review the potential usefulness, and superiority to current biomarkers, of plasma measurements of HNL Dimer in the monitoring of antibiotics in patients with sepsis. Future studies should be initiated to confirm this important aspect of sepsis management.